Tinjauan Yuridis Terhadap Mediasi Sebagai Sarana Penyelesaian Sengketa Perdata di Pengadilan Negeri Kelas Ib Kota Pekalongan : (Studi Putusan No.13/Pdt.G/2019/PN.PKL) - Umaroh, Umi; Yaqin, 'Alamul; Tri Handayani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The increase in civil cases that entered in the Court, prompting the MA to issue PERMA No. 1, 2016, on mediation procedures in court. The success of mediation in resolving cases in court is also found in the Pekalongan District Court, the Pekalongan District Court which has 2 (two) jurisdictions, namely Pekalongan City and Pekalongan Regency with data sources on the number of lawsuits from 2019 to December this is 46 (forty) six) cases, specifically cases with register number 13/Pdt.G/2019.PN.Pkl can be resolved through a mediation process without having to go through a long trial. This type of research is used libraryresearch with perprobleman this research 1) the mediation process and the obstacles faced in resolving civil disputes in the District Court Class IB Pekalongan City (Verdict No. 13 / Pdt.G / 2019 / PN.Pkl) 2) Juridical review of mediation practices conducted in resolving civil disputes in the District Court Class IB Pekalongan (Verdict No.13 / P Dt. G/2019/PN.Pkl). Teknik data collection used is library materials according to object studies. As for analyzing the data obtained, the author uses content analysis techniques. The results showed that: The Mediation Process that took place in the Pekalongan City Court Class 1B in decision No. 13 / Pdt.G / 2019 / PN.Pkl has been done well. In mediation conducted by mediators successfully help the parties to the dispute resolve the problem through mediation by agreeing to make peace with evidence of a deed of peace.